An Analysis of Speech Act Used in Teaching EFL; what are the Influences on the Students’ Learning and what are the Effect on Communicative Language Teaching Practices - Sujariati; Rampeng; Ika Sastrawati, Ika Sastrawati (Universitas Veteran Bangun Nusantara, 2025)
The primary objective of this research are to investigate the types of speech act used and produced through utterances in teaching process by lecturer in the class, and also need to know the influences of speech acts on students learning. The subject’s research goes to the lecturer and the English students at English department of Education Study Program of universitas Muhammadiyah Makassar. The data collected and analyzed through descriptive qualitative approach. The finding analyzed and displayed qualitatively. The findings showed up only two types of speech act used by lecturer namely; Locutionary act (expressive, directive) and Illocutionary act (assertive, directives, commisives, and expressives . Those are utterances used to function be a statement, command, asking question, and direction. Perlocutionary act itself showed up by students through their responding. The responses from students appeared in verbal by sentence, nonverbal by gestures, and any students gave responses both of them. Students claimed of The impact of the lecturers’ utterances on students’ Learning explained clearly namely can help the students to improve their understanding of implementation language competence, can increase their motivation in learning Pragmatic in English, enhance students to understanding speech act in term pragmatic in their communication, encourage them to imitate and practice speech act in appropriate way in communication and interaction both in the class and beyond the class. Hence, the use of speech act appropriately in teaching truly gave positive effect on communicative language teaching practices.